2015
DOI: 10.4238/2015.august.10.12
|View full text |Cite
|
Sign up to set email alerts
|

New compound heterozygous mutations of p. Thr101Ilefs*2 and p. Thr306Ale in a child from a Chinese family with 17α-hydroxylase/17, 20-lyase deficiency

Abstract: ABSTRACT. We determined whether a child with 17a-hydroxylase/17, 20-lyase deficiency possessed the sex-determining region (SRY) gene, and examined the mutations present in the CYP17A1 gene that led to 17a-hydroxylase/17, 20-lyase deficiency. In the child, karyotype analysis was performed and polymerase chain reaction analysis and electrophoretic techniques were used to identify the SRY gene. A total of 50 normal individuals were included as a control group. Polymerase chain reaction and DNA sequencing were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For example, Wu et al [24] reported a fifth exonic mutation in China, including a homozygous missense mutation c.796C>G (p.L266V) and a frameshift mutation, c.932_939delTTAAATGG (p.Val311Asp), which combines with an exon seven mutation (Y329fs) [25]. In addition, Xiao et al [26] reported a mutation of c.916A>G (p. Thr306Ale), constituting a compound heterozygous mutation with an additional mutation in the second exon (p. Thr101Ilefs*2). According to reports from abroad, Petri et al [22] highlight diverse missense and nonsense homozygous mutations in the fifth exon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wu et al [24] reported a fifth exonic mutation in China, including a homozygous missense mutation c.796C>G (p.L266V) and a frameshift mutation, c.932_939delTTAAATGG (p.Val311Asp), which combines with an exon seven mutation (Y329fs) [25]. In addition, Xiao et al [26] reported a mutation of c.916A>G (p. Thr306Ale), constituting a compound heterozygous mutation with an additional mutation in the second exon (p. Thr101Ilefs*2). According to reports from abroad, Petri et al [22] highlight diverse missense and nonsense homozygous mutations in the fifth exon.…”
Section: Discussionmentioning
confidence: 99%